Global and regional trends in COPD mortality, 1990-2010 - Burney,PGJ; Patel,J; Newson,R; Minelli,C; Naghavi,M (European Respiratory Journal, 2015)
Between 1990 and 2010, chronic obstructive pulmonary disease (COPD) moved from the fourth to third most common cause of death worldwide.Using data from the Global Burden of Disease programme we quantified regional changes in the number of COPD deaths and COPD mortality rates between 1990 and 2010. We estimated the proportion of the change that was attributable to gross national income per capita and an index of cumulative smoking exposure, and quantified the difference in mortality rates attributable to demographic changes.Despite a substantial decrease in COPD mortality rates, COPD deaths fell only slightly, from three million in 1990 to 2.8 million in 2010, because the mean age of the population increased. The number of COPD deaths in 2010 would have risen to 5.2 million if the age- and sex-specific mortality rates had remained constant. Changes in smoking led to only a small increase in age- and sex-specific mortality rates, which were strongly associated with changes in gross national income.The increased burden of COPD mortality was mainly driven by changes in age distribution, but age- and sex-specific rates fell as incomes rose. The rapid response to increasing affluence suggests that changes in COPD mortality are not entirely explained by changes in early life.